Comparative pharmacokinetic study of risedronate 35 mg healthy male subjects under fed conditions - Colaco, Socorrina; Ramesh, N.; Shabaraya, Ramakrishna (Research journal of pharmacy and technology, 2020)
The main objective of this research work was to evaluate the pharmacokinetics and the comparative oral bioavailability of newly developed Risedronate 35 mg test 1, test 2 and reference drug in 9 healthy male subjects under fed conditions. Single dose of either of the investigational products was administered orally in each period. A washout period of 7 days was provided between the following dosing days. The plasma concentrations of Risedronate were analyzed using a suitably validated LCMS/MS assay method. A calibration curve extending over the range 0.1974 ng/mL to 29.6121ng/mL with a LLOQ of 0.1974 ng/mL was used in subject sample analysis of Risedronate. Pharmacokinetic parameters Cmax, Tmax, AUCt, AUCinf, K el, T half were calculated for Risedronate. These pharmacokinetic parameters were calculated using the non-compartmental model of pharmacokinetic software. The two one-sided confidence intervals were calculated for the un-transformed and ln-transformed ratios of the pharmacokinetic parameters, Cmax, AUCt and AUCinf, for Bioequivalence of newly developed drug vs. Reference drug was equivalent in terms of rate of amount and absorption for Risedronate.